Neurophobia amongst medical students: Hype or reality - Suzanne Murphy; Emily Carey; Lena Dablouk; Jaifar Alomairi; Joy Maasarani; Jane BSQ. Ong; Khushboo Gupta; Riya Manas Sharma; Olivia McCracken; Deborah Shinyanbola; Abdulrahman Alrujaib; Rebecca Sheridan; et al. (Brain and Spine)
Introduction: ‘Neurophobia’ is a well reported phenomenon in the literature where in medical students and junior doctors have an inherent nervousness or ‘fear’ of neurology and neurosurgery. Research question: Why do less medical students choose neurology and neurosurgery as a career and identify if neurophobia is an ingrained belief or learned behaviour? Materials and methods: We developed a questionnaire to assess medical student views and beliefs in connection with a career in neurosurgery. Specifically we examined the following domains: considering a career in neurology and neurosurgery, confidence with neuro anatomy and pathology, traits associated with neurosurgeons and neurologists and finally, their perceived barriers to a neuro career. Results: 264 medical students completed the survey. Students from fourteen different medical schools across the world responded, with the highest number of students being from Irish medical schools. Over half of participants (58%) felt that neurology is an intimidating module and/or career choice while a huge 80% felt neurosurgery was an intimidating choice.We believe our research appears to be the first to open the survey to students across the world, with no limitations placed on region. Discussion and conclusion: Neurophobia is not limited to any one geographical region, age group or gender. It appears to be mainly be driven by an intimidation of the complex nature of neuroanatomy and neuropathology. This negative perspective can be further enhanced when students go on to have a negative experience on clinical attachments.